Mechanical property and microstructure of resistance spot welded twinning induced plasticity-dual phase steels joint. (1st August 2013) - Rajinikanth, V; Mukherjee, K; Ghosh Chowdhury, S; Schiebahn, A; Harms, A; Bleck, W
<x xml:space="preserve">Abstract</x> The present paper deals with the joining of twinning induced plasticity and dual phase steels, carried out by spot welding process with two different pulse durations (200 and 380 ms), by keeping other parameters constant. The microstructural and elemental analysis of the joints was characterised by optical microscopy and electron probe microanalyser. The mechanical properties of the joint were understood from microhardness measurements across the fusion zone as well as through shear and cross-tensile tests. The pulse duration of 380 ms has resulted in good macrostructure with negligible shrinkage void. It also shows smooth transition in hardness across the twinning induced plasticity steel/nugget/dual phase steel interfaces and good mechanical properties as compared to the joint prepared by pulse duration of 200 ms. Larger pulse duration results in sufficient time for the diffusion of alloying elements and yields negligible void formation due to Kirkendall effect.